Enhancing Beef Hamburger Quality: A Comprehensive Review of Quality Parameters, Preservatives, and Nanoencapsulation Technologies of Essential and Edible Oils - Tainara Santos Oliveira; Rogeria Comastri de Castro Almeida; Vanessa de Lima Silva; Cláudio Vaz Di Mambro Ribeiro; Leilson Rocha Bezerra; Camila Duarte Ferreira Ribeiro (Foods)
Essential and edible oils have applications in reducing oxidative processes and inhibiting the growth of microorganisms in meats and their derivatives, providing a natural alternative to synthetic preservatives. This preservative action meets the demand for clean labels and safe products, aiming to replace synthetic additives that pose potential health risks. Advances and limitations in applying essential and edible oils in meat preservation, highlighting their preservative properties or ability to improve nutritional profiles, are explored in this study. Despite the benefits, the direct application of oils faces limitations such as low solubility and sensory impact, which can be overcome by nanotechnology, including association with biopolymeric matrices, focusing on the protection of bioactive compounds and enhancing the functionality of natural oils in food systems. This approach is essential for innovation in food preservation, promoting safety and sustainability in the meat sector, and following consumer expectations and food safety guidelines. Studies suggest that by combining the functional benefits of essential and edible oils associated with nanotechnology, there can be significant contributions to innovation and sustainability in the meat sector, promoting natural preservation and meeting market regulations and expectations.